Penggunaan Media Digital Pengguanaan Media Digital dalam Proses Pembelajaran di Sekolah Dasar : Tantangan dan Peluang: Pengguanaan Media Digital dalam Proses Pembelajaran di Sekolah Dasar : Tantangan dan Peluang - Bunyamin, Nurmala; Haifaturrahmah; Nursina Sari (Journal of Practice Learning and Educational Development, 2026)
This study systematically examines the use of digital media in elementary school learning through a literature approach. The study covers the forms and implementation of digital media, its benefits in increasing student motivation and engagement, as well as challenges faced such as infrastructure limitations, teacher readiness, and content suitability. The results indicate that digital media can support independent learning and differentiation, but to overcome these obstacles, comprehensive teacher training, content development tailored to student needs, adequate infrastructure provision, and active parental involvement are required. This study concludes that with coordinated efforts, digital media can be effectively integrated to improve learning outcomes at the elementary school level.